Organizational Design and Environmental Performance: Clues From the Electronics Industry - Russo, Michael V.; Harrison, Niran S. (Academy of Management Journal, 2005)
A congruence model of organizational design suggests that direct reporting relationships between plant managers and environmental quality managers, monetary incentives for environmental performance, and coordination between environmental quality managers and business strategists reduce plant-level toxic emissions. We tested these relationships in a large sample of U.S. electronics facilities. Only a link between plant manager compensation and environmental performance reduced emissions. Subsequent analyses support a reverse causality, suggesting organizational characteristics result from (rather than cause) emissions performance and that firms remain reactive on environmental issues. These findings confront theories of environmental management and congruence with provocative questions, which we discuss in depth.